The Effect of Debt to Equity Ratio and Tax Avoidance on Firm Value in Food and Beverage Sub-Sector Manufacturing Companies Listed on the Indonesia Stock - Felecia; Armin Rahmansyah Nasution (Outline Journal of Economic Studies, 2023)
This study aims to determine the effect of Debt to Equity Ratio and Tax Avoidance on Firm Value partially and simultaneously in food and beverage sub-sector manufacturing companies listed on the Indonesia Stock Exchange (IDX). The population in this study is the food and beverage sub-sector manufacturing companies listed on the Indonesia Stock Exchange in the 2016 - 2020 period of 26 companies. Samples were taken as many as 11 companies using purposive sampling technique. T test results of the study partially show that the debt to equity ratio have a significant effect on firm value. T test results of the study partially show that the tax avoidance has not significant effect on firm value. Simultaneous research results show that debt to equity ratio and tax avoidance have a significant effect on firm value. The coefficient of determination (R²) shows that the firm value variable can be explained by the variables of debt to equity ratio, tax avoidance, while the rest is explained by other factors such as Current Ratio, Total Assets Turnover, Return on Equity dan Earning per share.